2003
DOI: 10.1128/jvi.77.24.13315-13322.2003
|View full text |Cite
|
Sign up to set email alerts
|

Novel System for the Simultaneous Analysis ofGeminivirus DNA Replication and Plant Interactions inNicotianabenthamiana

Abstract: The origin of replication of African cassava mosaic virus (ACMV) and a gene expression vector based on Potato virus X were exploited to devise an in planta system for functional analysis of the geminivirus replicationassociated protein (Rep) in transgenic Nicotiana benthamiana line pOri-2. This line contains an integrated copy of a tandem repeat of the ACMV origin of replication flanking nonviral sequences that can be mobilized and replicated by Rep as an episomal replicon. A Rep-GFP fusion protein can also mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…The karyophilic property of Rep of begomoviruses is consistent with its role during virus replication. Our results are in accordance with previous immunocytochemical staining of the Tomato golden mosaic virus (TGMV) Rep in infected plants (Nagar et al, 1995) and nuclear targeting of African cassava mosaic virus Rep-GFP fusion proteins (Hong et al, 2003). Our work further shows that a large Cterminal deletion (aa 131-359) in TYLCSV Rep does not prevent nuclear accumulation and suggests that the RGG sequence is not involved in this process.…”
supporting
confidence: 82%
“…The karyophilic property of Rep of begomoviruses is consistent with its role during virus replication. Our results are in accordance with previous immunocytochemical staining of the Tomato golden mosaic virus (TGMV) Rep in infected plants (Nagar et al, 1995) and nuclear targeting of African cassava mosaic virus Rep-GFP fusion proteins (Hong et al, 2003). Our work further shows that a large Cterminal deletion (aa 131-359) in TYLCSV Rep does not prevent nuclear accumulation and suggests that the RGG sequence is not involved in this process.…”
supporting
confidence: 82%
“…Moreover, efficient viral DNA replication also depends on interactions between Rep and the virus-encoded replication-enhancing protein and coat protein (Malik et al, 2005;Settlage et al, 2005), as well as with several other host factors (Bagewadi et al, 2004;Castillo et al, 2003;Kong & Hanley-Bowdoin, 2002;Luque et al, 2002;Settlage et al, 2001;Singh et al, 2007;Xie et al, 1999Xie et al, , 1995. Second, Rep of ACMV and related begomoviruses can elicit HR (Hong et al, 2003;Selth et al, 2004;van Wezel et al, 2002a). ACMV Rep and its homologue in tomato yellow leaf curl virus can also interact with the sumoylation system, which may participate in plant defence against pathogen infections (Castillo et al, 2004).…”
Section: Differentiation Of Rep-mediated Hr and Dna Replicationmentioning
confidence: 99%
“…PCR detection using primers P1 and P2 (Hong et al, 2003) (Fig. 2a) demonstrated that Rep-GFP or Rep*-GFP expressed from PVX/Rep-GFP or PVX/Rep*-GFP, respectively, could mobilize the episomal replicon in pOri-2 plants to produce the diagnostic 1.64 kb DNA fragment, which could only be generated from the circular molecules (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations